The Problem of Islamic Risk: According to the Western vision between reality and assumption "Historical Study" - Nassif, Nazhan Hammoud; KAsay, Hossam (Journal of Tikrit University for Humanities, 2018)
The study of the political phenomenon as one of the fields of social phenomenon is no less important than the emphasis on history and history. To study any political phenomenon, history must be used as a methodological and scientific tool. It is a return to the roots of the phenomenon. The emergence of Islam on the scene of political events as a kind of retreat and return to times of absence, how how to live in the twentieth century to return to the Middle Ages and the alliance of fundamentalism with colonial trends throughout the political history of nations. Christian fundamentalists and their religious interpretations stemming from the Bible - the Old Testament - in America show similar trends with what the Zionists say